2008
DOI: 10.1002/hbm.20551
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation and accommodation patterns in ventral occipitotemporal cortex in learning a second writing system

Abstract: Using fMRI, we compared the patterns of fusiform activity produced by viewing English and Chinese for readers who were either English speakers learning Chinese, or Chinese-English bilinguals. The pattern of fusiform activity depended on both the writing system and the reader's native language. Native Chinese speakers fluent in English recruited bilateral fusiform areas when viewing both Chinese and English. English speakers learning Chinese, however, used heavily leftlateralized fusiform regions when viewing E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
133
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 54 publications
22
133
1
1
Order By: Relevance
“…In our study, we observed activation during character reading near this same ''Chinese region,'' at the left dorsal inferior frontal gyrus (BA9). The peak was at (À50, 2, 34), very close to the peaks of (À48, 4, 35) and (À44, 4, 33) for learners in Nelson et al (2009) and Liu et al (2007), respectively, and to the peaks of (À48, 9, 30) and (À46, 8, 34) for native Chinese speakers in Bolger (2005) and Cao (2010), respectively. This convergence of findings suggests that English speakers can adopt the procedures of addressed retrieval of phonology and semantics after only a short period learning Chinese.…”
Section: Differences Between Chinese and Englishsupporting
confidence: 51%
See 3 more Smart Citations
“…In our study, we observed activation during character reading near this same ''Chinese region,'' at the left dorsal inferior frontal gyrus (BA9). The peak was at (À50, 2, 34), very close to the peaks of (À48, 4, 35) and (À44, 4, 33) for learners in Nelson et al (2009) and Liu et al (2007), respectively, and to the peaks of (À48, 9, 30) and (À46, 8, 34) for native Chinese speakers in Bolger (2005) and Cao (2010), respectively. This convergence of findings suggests that English speakers can adopt the procedures of addressed retrieval of phonology and semantics after only a short period learning Chinese.…”
Section: Differences Between Chinese and Englishsupporting
confidence: 51%
“…That learners with just over one term of study show activation patterns typical of skilled native language Chinese readers demonstrates the accommodation of the brain's reading network to the demands of the writing system Nelson et al, 2009]. For example, the bilateral activation of fusiform gyri and middle occipital gyri for Chinese suggests a role for holistic visual configuration in the right hemisphere, in addition to the left hemisphere role in more fine-grain (e.g.…”
Section: Differences Between Chinese and Englishmentioning
confidence: 99%
See 2 more Smart Citations
“…51 The left angular gyrus has also been mentioned as a cortical locus of writing. 50 The other areas associated with writing are left superior parietal lobe, 52 left posterior inferior temporal cortex, 53 bilateral ventral occipitotemporal cortex, 54 and thalamus. 52 These studies indicate that the parietal lobe is the most important lobe for reading and writing.…”
Section: Discussionmentioning
confidence: 99%